Dry Reforming and Reverse Water Gas Shift: Alternatives for Syngas Production?. Issue 4 (4th February 2015) - Schwab, Ekkehard; Milanov, Andrian; Schunk, Stephan Andreas; Behrens, Axel; Schödel, Nicole; Machhammer, Otto
Abstract Dry reforming and reverse water gas shift are often discussed as potential carbon dioxide sinks. They may in the near future act as enablers for improving carbon footprints of certain value chains. In this paper, it will be critically discussed in short format why both technologies can only be operated economically and sustainably in defined contexts. A number of technical and economic challenges of both reactions are discussed and potential solutions for technical realization are presented.